2018
DOI: 10.1111/jocn.14527
|View full text |Cite
|
Sign up to set email alerts
|

Evolving self view and body image concerns in female postoperative bariatric surgery patients

Abstract: To date, the primary measure of bariatric surgery success has focused almost exclusively on the amount of weight loss. Implementing psychological as well as physiological care, however, may be the key to full recovery and long-term success. Practitioners can use this new information to plan effective pre- and postoperative psychological preparation and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
4
28
0
4
Order By: Relevance
“…The ND risk for perioperative positioning injury presented the risk factor obesity most prevalent in adults, which requires attention in the prevention of damage and injuries in the postoperative period (29) . The ND risk for infection, damages on skin and in dentition are expected in the surgical clinic patient (24)(25) corroborating the results shown in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The ND risk for perioperative positioning injury presented the risk factor obesity most prevalent in adults, which requires attention in the prevention of damage and injuries in the postoperative period (29) . The ND risk for infection, damages on skin and in dentition are expected in the surgical clinic patient (24)(25) corroborating the results shown in this study.…”
Section: Discussionsupporting
confidence: 89%
“…In the domain of nutrition, a characteristic for the identification of overweight and obesity was BMI. Such changes may increase the risk for surgical complications such as infections, atelectasis, fistulas, bleeding and dehiscence (24) . In the activity/rest domain, the characteristics of dissatisfaction with sleep and alteration in the sleep pattern, reported by adults and elderlies, were those that determined the selection of the ND disturbed sleep pattern.…”
Section: Discussionmentioning
confidence: 99%
“…As regards, dermatoses affect general health, well-being, and social adaptation of the individual (3)(4)(5). In a study, the majority of the female patients who were candidates for Bariatric Surgery declared high body image concerns (6). Modern cognitive approaches to Body Dysmorphic Disorder suppose that appearance-related intrusive cognitions and their functional outcomes determine the disorder (1).…”
Section: Dear Editormentioning
confidence: 99%
“…The Body Dysmorphic Disorder is a common debilitating disease worldwide. Patients manifest a disabling preoccupation with a few perceived defects, frequently well-marked by poor insight or delusional thoughts (2)(3)(4)(5)(6)(7). According to the results of a study, rhinoplasty candidates reported high body image concern (8).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation